Penguatan Karakter Peduli Sosial Pembelajaran IPS di SMP Muhammadiyah Al-Kautsar PK Kartasura Pada Era New Normal - Ridho, Sadam (EduPsyCouns: Journal of Education, Psychology and Counseling, 2023)
Strengthening Character Education (PPK) consists of social care characters applied at Muhammadiyah Al-Kautsar Junior High School PK Kartasura. The purpose of this study is to strengthen the social care character of students through social studies learning. This research uses a type of qualitative descriptive research, which is research intended to describe a situation that describes and describes the implementation of social care characters through social studies learning. The research method used in this study is a case study method. As well as the data collection method used in this study is to use observation and interview techniques, then the collected data will be analyzed using triangulation techniques. The focus of this research is strengthening the social care character of students through social studies learning.